FEATURES OF THE "MASK" PROJECTIVE TECHNIQUE FOR DIAGNOSING THE MENTAL STATES OF MILITARY PERSONNEL – COMBAT VETERANS - Kravchenko, Kateryna; Chernikov, Vladyslav (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2025)
B a c k g r o u n d . The experience of combat actions on the territory of Ukraine made it possible to state that psychological counseling with combatants has its own specifics. Combatants often face difficulties in verbalizing their mental states and experiences, and dissimulation of traumatic experiences is quite common. The negative consequences that can lead to the avoidance of their own experiences by combatants necessitate not only new approaches to providing them with psychological assistance, but also the development and use of psychodiagnostic tools when working with soldiers, which would take into account all the specific features of military service, especially in combat. One such method is the use of projective techniques (including metaphorical associative maps). M e t h o d s . The study was conducted in three stages: 1) development of the "Mask" metaphorical associative maps (2022–2023); 2) creation of a projective methodology based on images of metaphorical associative maps (2024); 3) testing of the projective methodology (late 2024 – early 2025). At these stages of the study, the methods of theoretical and empirical research were used. Among the empirical research methods, the following ones were used: testing, surveys, observation, interview, method of expert evaluation and experimental research. Methods of mathematical statistics were used to process the outcomes obtained. It should be noted that the methodology of the study made it possible to assert the validity and reliability of the methodology. R e s u l t s . The "Mask" projective technique allows diagnosing 17 mental states of military personnel: 1) normal state; 2) apathy; 3) communication issues; 4) grief; 5) fear of being punished; 6) neuropsychiatric instability; 7) adaptation problems; 8) mental disorders; 9) mental exhaustion; 10) aggression; 11) obsessive thoughts; 12) suicidal risks; 13) internal conflict; 14) resentment; 15) cognitive impairment; 16) fear; 17) reluctance to speak out (resistance to discuss their own experiences). The article also outlines the advantages and disadvantages of this methodology, as well as recommendations for its implementation. C o n c l u s i o n s . The outcomes of the study confirm the effectiveness of the "Mask" projective technique as a diagnostic tool for assessing the mental states of military personnel – combat veterans. The technique highlights a high sensitivity to the psychological issues encountered by combatants and allows the identification of a wide range of mental conditions.